Podcast como herramienta para contar nuestro territorio. Textos explicativos orales de estudiantes de grado séptimo (2023)
The present degree work, which is a research monograph, addresses the topic of orality and its importance in the academic field. The main objective of this research is to strengthen oral competence through oral explanatory texts in seventh grade students at the Liceo los Ángeles school, through the production of podcast